1999
DOI: 10.1111/j.1572-0241.1999.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal and Gastric Nitric Oxide Synthesizing Innervation in Primary Achalasia

Abstract: Our results indicate that achalasia is a motor disorder with an intrinsic inhibitory denervation of the esophageal and gastric component of the LES and of the proximal stomach, thus providing further evidence for an extraesophageal extension of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…In line with an immune-related mechanism, recent data from Moses et al [6] demonstrated that the serum of 51% of patients with idiopathic achalasia contained circulating anti-neuronal antibodies labelling all oesophageal myenteric neurons and ileal myenteric and submucosal neurons of the guinea-pig. In contrast to what one could expect, anti-neuronal antibodies did not appear to target selectively nitrergic inhibitory motor neurons [6], which are known to be markedly reduced in achalasia [17]. Further studies brought evidence that circulating autoantibodies bind to oesophageal myenteric neurons by recognising a 62 kDa protein expressed by neurons of the upper gastrointestinal tract [6,18].…”
Section: Discussionmentioning
confidence: 95%
“…In line with an immune-related mechanism, recent data from Moses et al [6] demonstrated that the serum of 51% of patients with idiopathic achalasia contained circulating anti-neuronal antibodies labelling all oesophageal myenteric neurons and ileal myenteric and submucosal neurons of the guinea-pig. In contrast to what one could expect, anti-neuronal antibodies did not appear to target selectively nitrergic inhibitory motor neurons [6], which are known to be markedly reduced in achalasia [17]. Further studies brought evidence that circulating autoantibodies bind to oesophageal myenteric neurons by recognising a 62 kDa protein expressed by neurons of the upper gastrointestinal tract [6,18].…”
Section: Discussionmentioning
confidence: 95%
“…8,9 A number of lines of experimental evidence suggest that a deficit of nitric oxide generating neurons is primarily responsible for the motor abnormalities seen in achalasia. 10,11 The manometric criteria used to diagnose achalasia are aperistalsis of the smooth muscle portion of the esophageal body, and failed or less than complete relaxation of the LES during swallowing. 6,7 However, a subset of patients with achalasia showed other findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the LES, nNOS appears to be the major enzymatic source of NO (Kim et al 1999;Lefebvre 1995), and a reduction in nNOS expression (which is associated with impaired NO synthesis) is thought to be responsible for gastrointestinal motility dysfunction, such as that observed in achalasia (Takahashi 2003). A reduction in NOS activity and a loss of NOS-containing neurons in the esophageal myenteric plexus have both been observed in patients with sporadic achalasia and Allgrove syndrome, and these abnormalities are correlated with disease severity (De Giorgio et al 1999;Gockel et al 2008;Khelif et al 2003;Lui et al 1997;Mearin et al 1993;Watanabe et al 2002). Furthermore, Nos1 (nNos)-deficient mice display LES hypertension and impaired relaxation which mimics human achalasia (Sivarao et al 2001).…”
Section: Candidate Genes Mediating Esophageal Motor Functionmentioning
confidence: 93%
“…NO is synthesized from L-arginine by nitric oxide synthases (NOS) (De Giorgio et al 1999;Gockel et al 2008;Kim et al 1999;Lefebvre 1995;Lui et al 1997;Mearin et al 2006;Mearin et al 1993;Murray and Clark 1994;Sanders et al 2002;Sivarao et al 2001;Takahashi 2003;Watanabe et al 2002), and three forms can be distinguished: neuronal NOS (nNOS), inducible NOS (iNOS), and endothelial NOS (eNOS) (Mearin et al 2006). These are encoded by three different genes: NOS1 (nNOS), NOS2 (iNOS), and NOS3 (eNOS), which are located on chromosomes 12q24, 17q11, and 7q36, respectively (Mearin et al 2006).…”
Section: Candidate Genes Mediating Esophageal Motor Functionmentioning
confidence: 98%